Online Learning: Problems Experienced by Students in Educational Supervision Courses - Rahman Peliza; Muhammad Munawir Pohan (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aimed to describe some of the problems students face in online learning in educational supervision courses in the Kerinci Regency. This type of research is classified as a qualitative research type. This study enrolled four fifth semester students, two from class B and two from class D. The data collection techniques used in this study were observation and interviewing. The techniques used in data analysis include data collection, data reduction, presentation and conclusion. Credibility, dependability, and confirmability tests can be used to determine validity. The research phase entails the following activities: theme selection, literature review, formulation of the research objective and difficulty, data collection, data refinement, data processing, data analysis, theoretical dialogue, triangulation of findings, and research conclusions. The research findings indicate that: (1) the internet network is frequently disrupted, resulting in material explained by lecturers via zoom meetings not sounding clear and being misunderstood by students; (2) some students lack access to learning tools such as laptops and androids, which slightly impede the lecture process and group discussions during zoom meetings; and (3) the level of seriousness and activeness of students in participating in online lectures through zoom meetings is still not good.